1992
DOI: 10.1007/bf01297422
|View full text |Cite
|
Sign up to set email alerts
|

Chlorate electrosynthesis current efficiency equations based on dimensionless groups

Abstract: Various mathematical models for the electrosynthesis of chlorate are anatysed taking into account that the current efficiency is mainly affected by the distribution of the two competing reactions forming chlorate, i.e. the anodic oxidation and the autoxidation of hypochlorite. It is shown that the current efficiency is determined by four dimensionless groups one of which is commonly negligible. Results are compared with a known current efficiency equation. Two new current efficiency equations, representing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The results of the influence of anode current density on current efficiency are shown in Table , which clearly indicates that the current efficiency increases with increasing anode current density. This is in conformity with results reported ,, earlier. However, the IR drop increases linearly with the current density, resulting in an increase of cell voltage and consequently higher energy consumption.…”
Section: Resultssupporting
confidence: 94%
“…The results of the influence of anode current density on current efficiency are shown in Table , which clearly indicates that the current efficiency increases with increasing anode current density. This is in conformity with results reported ,, earlier. However, the IR drop increases linearly with the current density, resulting in an increase of cell voltage and consequently higher energy consumption.…”
Section: Resultssupporting
confidence: 94%
“…Vogt 18 empirically investigated a majority of the previous models and came to the conclusion that the elctrochemical reactor acts basically like a plug-flow reactor, the consumption of hypochlorite occurring through its oxidation to chlorate and oxygen. He concluded that mixing in the axial direction was small, so that the hypochlorite concentration decreases linearly from the inlet to the outlet, and this concentration gradient defines transport from the bulk to the respective electrodes.…”
mentioning
confidence: 99%
“…A model assuming ideal stirred-tank-reactor conditions for both the electrochemical and the chemical reactor [214] was compared with industrial results [180]. A more recent model combines a plug flow electrolyzer with either a stirred tank or a plug flow chemical reactor [217]. The results show satisfactory agreement with data from two industrial systems [218].…”
Section: Operational Parametersmentioning
confidence: 92%